SOME OF SEROLOGICAL MARKERS DURING PELVIC PAIN CAUSED BY ADENOMYOSIS - M. R. Orazov (IRBIS LLC, 2016)
One of the dominant clinical symptoms of adenomyosis is chronic pelvic pain . Chronic pelvic pain is recurrent or persistent pain that bothers patient less than 6 months. The aim of the study was to determine the clinical informativeness use of oncological markers CA-125 and NOT-4 in blood serum of women with pelvic pain caused byadenomyosis. In the present study included 63 patients adenomyosis - as a core group, and 30 apparently healthy women of reproductive age as a comparison group. Indicators CA-125 were higher in patients in the second subgroup with moderately severe pain syndrome, and the average at the time of treatment amounted to 45-63 U/ml, P<0.001), but on the second day of the menstrual cycle indicators again increased and averaged 54-70 U/ml ,and also significantly (P<0.001) decreased in the study after the end of the regular menstruation( 1st-2nd dry day after menstruation in the framework of the first phase of the menstrual cycle and averaged 42-60 U/ml compared with the comparison group apparently healthy women-8.9 IU/ml Conclusion , the evidence suggests that women with pelvic pain syndrome adenomyosis is the place to co-proliferative endometrial pathology. And in these cases increasyse the sensitivity of the above serological markers. The use of two markers (NOT-4 and CA-125) has a more accurate diagnostic value to identify the process of malignization in the reproductive organs, and it is important for differential diagnosis of hyperplastic processes, and for early diagnosis of endometrial adenocarcinoma.